74.1k views
3 votes
Solve the simultaneous equation
2x+3y=13
4x-y=-2

User ZviBar
by
5.6k points

2 Answers

3 votes

Answer:

(1/2, 4)

Explanation:

First, multiply the first equation by 2, so the 2x becomes 4x:

4x + 6y = 26

4x - y = -2

Now that we multiplied the first equation by 2, we can subtract the 2 equations to get rid of x and solve for y:

7y = 28

y = 4

Now we know y, we can plug y as 4 into any of our previous equations and solve for x:

4x - 4 = -2

4x = 2

x = 1/2

Therefore, the solution to this system of equations is (1/2, 4).

User Avinash Jadhav
by
5.5k points
4 votes

Answer:

In order to find the unknown variables x and y we need to simplify these equations in the way that will make it possible for us to get rid of either x or y variable, and make it easier to solve the remaining variable.

This method is known as Elimination, which is one of the methods how to solve a system of linear equations.

We need to rewrite the equations so that when the equations are added, one of the variables is eliminated. In simple terms, we need to get same number of x's or the same number of y's, but with an opposite sign, in both equations.

(1) 2x - 3y =13

(2) 3x + y = 3

You can multiply equation (2) by 3, then add equations (1) and (2) to form equation (3) with just one variable.

(2) 3*(3x+y) = 3*(3)

(2) 9x + 3y = 9

(1) 2x - 3y = 13

(3) 9x + 3y + 2x - 3y = 9 + 13

(3) 11x = 22

(3) x = 2

Then substitute our value for x back to one of the original equations and find what the value of y is.

2x - 3y = 13

2*(2) - 3y = 13

4 - 3y =13

- 3y = 9

y = - 3

Afterwards we can check our results by substituting our variables back into the original equations.

2*(2) - 3*(- 3) = 13

3*(2) + (- 3) = 3

Problem solved :)

Explanation:

User Maksadbek
by
5.9k points